The dramatic COVID 19 outbreak in Italy is responsible of a huge drop of urological surgical activity: a multicenter observational study. (19th October 2020) - Rocco, Bernardo; Sighinolfi, Maria Chiara; Sandri, Marco; Altieri, Vincenzo; Amenta, Michele; Annino, Filippo; Antonelli, Alessandro; Baio, Raffaele; Bertolo, Riccardo; Bocciardi, AldoMassimo; Borghesi, Marco; Bove, Pierluigi; et al.
Abstract : Objective: To describe the trend in surgical volume in urology in Italy during the coronavirus disease 2019 (COVID‐19) outbreak, as a result of the abrupt reorganisation of the Italian national health system to augment care provision to symptomatic patients with COVID‐19. Methods: A total of 33 urological units with physicians affiliated to the AGILE consortium (Italian Group for Advanced Laparo‐Endoscopic Surgery; www.agilegroup.it ) were surveyed. Urologists were asked to report the amount of surgical elective procedures week‐by‐week, from the beginning of the emergency to the following month. Results: The 33 hospitals involved in the study account overall for 22 945 beds and are distributed in 13/20 Italian regions. Before the outbreak, the involved urology units performed overall 1213 procedures/week, half of which were oncological. A month later, the number of surgeries had declined by 78%. Lombardy, the first region with positive COVID‐19 cases, experienced a 94% reduction. The decrease in oncological and non‐oncological surgical activity was 35.9% and 89%, respectively. The trend of the decline showed a delay of roughly 2 weeks for the other regions. Conclusion: Italy, a country with a high fatality rate from COVID‐19, experienced a sudden decline in surgical activity. This decline was inversely related to the increase in COVID‐19 care, with potential harm particularly in the oncological field. The Italian experience may be helpful for future surgical pre‐planning in other countries not so drastically affected by the disease to date.